The relationship between intervertebral disc pathologies and the use of digital devices and lack of physical activity in adolescents: Disc pathologies, digital devices, and physical activity - Ozmaden Hantal, Asli; Iptec, Murat (Journal of Surgery and Medicine, 2024)
Background/Aim: Existing research on herniated discs in adolescents primarily focuses on surgical interventions and outcomes, with fewer studies investigating the effectiveness of non-surgical therapies. The correlation between obesity, facet tropism, lumbosacral transitional vertebrae, trauma, certain sports activities, and herniated discs in adolescents is well-documented. Comparable to adults, a sedentary lifestyle in adolescents potentially carries a significant risk of developing disc degeneration and herniation. Consequently, this study aims to examine the relationship between increased digital device usage, decreased physical activity, and the onset of disc pathologies in adolescents. Methods: The study group included 94 patients aged between 10 and 16 years diagnosed with cervical (CDH), thoracic (TDH), and lumbar (LDH) disc disease. For each participant, the individual daily usage time spent on desktop computers, tablets, laptops, and mobile phones and the total time spent on all digital devices were evaluated. Their level of physical activity was also assessed using the International Physical Activity Questionnaire – Short Form (IPAQ-SF). The study eliminated causes such as listhesis, facet tropism, lumbosacral transitional vertebra, trauma, and sports injuries that could prompt the development of these spinal pathologies. Additionally, other conditions that might cause spinal pain, such as scoliosis, rheumatological diseases with spinal involvement, tumors, and myofascial pain, were also ruled out. Results: The average age of all patients was 13.44 (2.07) years. A majority were women (n=55), comprising 58.50% of the sample. Of the patients, 60.64% had CDH, 12.77% had TDH, and 75.53% had LDH. The amount of physical activity and time spent on digital devices were similar across both genders (P=0.194 and P=0.770). A significant correlation was found between CDH and the time spent on tablets, laptops, and mobile phones (P<0.001). Again, a significant correlation was observed between LDH, usage of desktop computers, total time spent on all digital devices, and the IPAQ-SF score for low physical activity (P<0.001). Conclusion: The prevalence and duration of digital device use among adolescents are increasing, while physical activity is decreasing. Our study indicates that this situation may be linked to the development of disc degeneration and hernias. Understanding this association can help reduce treatment and rehabilitation costs and prevent the potential loss of workability and quality of life resulting from a herniated disc. Consequently, additional comparative research on this topic is crucial.